Analysis Of Economic And Psychological Aspects Of Melancholic Personality Of Character Dialogue In The Collection Of Short Stories Love Of Ordinary Men By Asma Nadia Et Al - Masni, Harbeng; Budiningtyas, Dwi Putri; Zahar, Erlina; Rahim, Arif; Adriani, Evi; Palupi, Retno Maria; Azizah, Azizah; Andriani, Lili; Tara, Firman; Hutabarat, Zuhri Saputra; Sujoko, Sujoko (LLDIKTI Wilayah 1 Sumatera Utara, 2024)
The purpose of this study is to describe the manifestation of the economic and melancholic personality aspects of the main characters in the short story collection Cinta Laki-laki Biasa by Asma Nadia et al. The benefits obtained practically and theoretically are to provide knowledge to readers about literary works, especially on the aspects of the form of melancholic personality contained in the short story collection, useful for the author himself, and as input regarding the interests and implementation of education, especially literature teaching. This research is a qualitative research that is taken in the form of sentences, paragraphs of dialogue and excerpts of dialogue in paragraphs that contain aspects of the form of melancholic personality. The data source in this study is the short story collection Cinta Laki-laki Biasa by Asma Nadia et al. Data analysis resulted in several studies of aspects of the form of melancholic personality in the main characters. Based on the research results, it can be concluded that the collection of short stories Cinta Laki-laki Biasa by Asma Nadia et al. contains aspects of melancholic personality in the main characters in each short story, especially the short story Cinta Laki-laki Biasa by Asma Nadia which is the cover title of this short story collection, so it is still possible for several other studies to reveal the problems presented in the collection of short stories Cinta Laki-laki Biasa by Asma Nadia et al.